Manajemen POAC Wakaf Di Indonesia (ZISWAF: Jurnal Zakat dan Wakaf, 2020)
A company succeeds if management is good. There are many reports of waqf land disputes on waqf institutions. That way it requires tracking the management of waqf management. Given, that the waqf institution is a public organization which certainly requires a good organizational system. Therefore, this journal discusses the management of waqf POAC in Indonesia. This research is a qualitative descriptive study. Which is to explain and evaluate the management system in the management of waqf through management functions, namely Planning, Actuating, Organizing, and Controlling. Sources of data in this study come from literature, results of previous studies and facts in the field found by the authors. In accordance with POAC Management that Waqf in Indonesia is not optimal. It can be seen from the planing that has not yet been realized, Organizing which is not optimal in assigning tasks, actuating is not optimal, it can be seen from the many reports of public complaints to the Indonesian Waqf Board and Controling has not been done because it is only done when finding reports.